Software de gestión de las direcciones y unidades de producción en la empresa pública ESPAM MFL – EP - Carranza Loor, Jonathan Jesús (2018)
The objective of this work was to develop a software to manage the information of the addresses and production units in the public company ESPAM MFL - EP, which was achieved through the application of the Agile Scrum development methodology that, having a framework of work divided into three phases allowed the effective collaboration of the project team; in the planning and architecture phase, the database was designed according to the requirements for the software. In the execution phase of the development, the application was made using the Asp.net Indentity languages in conjunction with the Entity Framework approach "Code First" and for the inspection and adaptation phase of the development, the user interfaces were adapted according to the business standards and then proceed with the installation and configuration of the system. The final result was a comparative analysis of the time it took to manage the documents with and without the system, showing a reduction of 79.72% of the time used, the optimization and the benefit that the system represents for the institution.